Manajemen Risiko Electronic Nursing Documentation (END) - ryan priambodo; Pudji agung Wibowo; Aris Suprianto; Ana Zakiyah (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2026)
Introduction : Electronic Nursing Documentation (END) systems have become a critical component of modern nursing practice, yet their implementation introduces multiple risks that may threaten patient safety and care quality. This study aimed to identify, analyze, and mitigate potential risks associated with END implementation at X Hospital. Method : A descriptive risk management approach was applied using the five-step framework: risk identification, analysis, mitigation, implementation, and evaluation. Data were collected through incident reviews, nurse satisfaction surveys, direct observation, and brainstorming with nursing, IT, and management teams. Risks were analyzed using a 5×5 Risk Matrix and prioritized for mitigation. Result : Ten major risks were identified across technical, clinical, human resource, legal, and organizational domains. The highest-risk events were medication dosage input errors and patient misidentification (risk score 20, “extreme”). Mitigation strategies included user interface redesign, barcode medication administration, auto-logout, patient photo integration, competency-based training, and downtime protocols. After a 12-month phased implementation, expected outcomes included a 75% reduction in END-related incidents, documentation completeness above 95%, and nurse satisfaction improvement to 85%. Discussion : Systematic risk management for END can significantly enhance patient safety and documentation quality. Key success factors include strong managerial commitment, comprehensive nurse training, responsive IT support, and a continuous improvement culture.